2002
DOI: 10.3171/jns.2002.96.3.0523
|View full text |Cite
|
Sign up to set email alerts
|

Brachial plexus neurotization with donor phrenic nerves and its effect on pulmonary function

Abstract: When the right phrenic nerve is used as a donor in neurotization of the musculocutaneous nerve, the patient incurs a higher risk of reduced pulmonary VC. If possible, the left phrenic nerve should be preferred. The Pi(max) has to be determined preoperatively to avoid any further decrease in the already reduced pulmonary function due to the initial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 20 publications
1
30
0
5
Order By: Relevance
“…Luedemann et al reported a series of 23 patients who underwent neurotization surgery with the phrenic nerve as the donor nerve and found that none of the 23 patients experienced pulmonary problems postoperatively; however, the patients incurred a higher risk of reduced pulmonary VC when using the right phrenic nerve than the left one. The authors suggested that if possible, the left phrenic nerve should be used [28]. Based on the above results and those of our previous report [11], we used the left phrenic nerve for transfer in all patients in the present study; none of them experienced pulmonary problems following the surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Luedemann et al reported a series of 23 patients who underwent neurotization surgery with the phrenic nerve as the donor nerve and found that none of the 23 patients experienced pulmonary problems postoperatively; however, the patients incurred a higher risk of reduced pulmonary VC when using the right phrenic nerve than the left one. The authors suggested that if possible, the left phrenic nerve should be used [28]. Based on the above results and those of our previous report [11], we used the left phrenic nerve for transfer in all patients in the present study; none of them experienced pulmonary problems following the surgery.…”
Section: Discussionmentioning
confidence: 62%
“…nerve (3,11,19,23,24). The best outcome of neurotization can be expected in short denervation times and in the presence of proximal healthy roots (4).…”
Section: Mohammad-reda A: Early Post-operative Results After Repair Omentioning
confidence: 99%
“…The second drawback to the use of the phrenic nerve is that its harvest usually results in decline of pulmonary function, 34 at least temporarily; and more significantly affecting the right hemithorax. 35 This is a problem chiefly in infants susceptible to recurrent upper respiratory tract infections and in adults with impaired cardiac or pulmonary function. Most authors do not recommend the use of the phrenic nerve in these patients.…”
Section: Donor Nervesmentioning
confidence: 99%